ANALYSIS OF THE IMPACT OF DIFFERENT DISTRIBUTED GENERATOR TECHNOLOGIES ON HARMONIC VOLTAGES (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
While distributed generators (DGs) can reduce carbon dioxide emissions, they can also cause disturbances and lead to power quality (PQ) issues, with harmonic voltages being an important parameter to consider. In this paper, the impact of 14 connected photovoltaics (PVs) and a small hydropower plant (sHPP) on harmonic voltage distortions in a real medium voltage (MV) and low voltage (LV) distribution network in Bosnia and Herzegovina was analyzed. Simulation tools carried out by DigSILENT PowerFactory offer a wide range of advantages that give system operators the ability to have insight into PQ behavior in the presence of intermittent renewable energy sources (RES). Due to the inverter-based electricity generation, PV power plants inject harmonics into the LV network. The impact is relatively small and does not violate the limits from the European PQ standard EN 50160 due to the relatively small power of the modelled existing PVs. However, integrating additional PVs could lead to a violation of limits. Therefore, where a large power of PV power plants is installed, if it is possible to integrate sHPP, they will contribute to the reduction of generated harmonics without the need to reduce the power of PV. The contribution of this paper is that it compares the impact of different power generation technologies on harmonic voltages using data from a real network rather than a test network.
Keywords: Harmonic voltages; Photovoltaic (PV); Small hydropower plant (sHPP); Distribution network; Power quality (PQ)